Transnational Japan as history empire, migration, and social movements - Iacobelli, Pedro; Leary, Danton; Takahashi, Shinnosuke (Palgrave macmillan transnational history series, 2016)
"This volume looks at the history of Japan from a transnational perspective. It brings to the fore the interconnectedness of Japan's history with the wider Asian-Pacific region and the world. This interconnectedness is examined in the volume through the themes of empire, migration, and social movements"